PENGARUH PELAYANAN FISKUS DAN PENGETAHUAN PERPAJAKAN TERHADAP KEPATUHAN WAJIB PAJAK (Studi Empiris terhadap Wajib Pajak di Semarang Tengah) - Yuli Anita Siregar; Saryadi Saryadi; Sari Listyorini (Universitas Diponegoro, 2012)
ABSTRACT Tax payer compliance in paying tax need to realize the target of tax. Tax payer compliance can be affected by fiskus service and knowledge of taxation. In pra survey can be found the problem which there has been increasing the tax payers in Semarang Tengah, that followed by increasing the delinquent tax payers. The research problem is: are fiskus service and knowledge of taxation affect tax payer compliance? Meanwhile, the purpose of this research is to knowing the effect of fiskus service and knowledge of taxation toward tax payer compliance. Population of this research are the tax payers UMKM Semarang Tengah that counted 7.648. Sampling technique is purposive sampling, which counted 100 participants. Data collecting method use questionnaire with validity and reliability analysis. Data analysis method is multiple linear regression. The result show that fiskus service include good categories, knowledge of taxation include very good categories, tax payer compliance include very high categories. There is significant effect between fiskus service and knowledge of taxation toward tax payer compliance simultaneously about 39,4%. From the result, we can conclude that there are significant effect between fiskus service and knowledge of taxation toward tax payer compliance. This can be looked from t-counted value higher than t-table so hypothesis of this research is accepted. The suggestion of this research are KPP Pratama Semarang Tengah I must be uphold to the law of taxation and for the tax payers must be understanding lay od tax and realize how important to pay tax in time.